Playing the Odds - Johnson, Soren (The Best Writing on Mathematics 2013, 2014)
One of the most powerful tools a designer can use when developing games is probability, using random chance to determine the outcome of player actions or to build the environment in which play occurs. The use of luck, however, is not without its pitfalls, and designers should be aware of the tradeoffs involved—what chance can add to the experience and when it can be counterproductive. One challenge with using randomness is that humans are notoriously poor at evaluating probability accurately. A common example is thegambler’s fallacy,which is the belief that odds even out over time. If the